Heutagogy Approach in Social Study Learning - Saepudin, Aep (Jurnal Ilmiah Dozen Globalindo, 2019)
In the last few years, the Heutagogy approach had begun to be re-discussedand applied in education after more than a decade of being less popular withthe pedagogical and andragogical approaches. The education sector frombasic to tertiary education has begun to adapt to the development oftechnology and information in the industrial revolution 4.0, especially in theeffort to encourage the effectiveness of different ways of learning andteaching.The method used in this study is literature review by presenting the definitionof heutagogy and describing how heutagogy is implemented in social studylearning. In the Heutagogy approach, students are asked to decide what tolearn and how to learn. Therefore, control the learning process in the learnerand the teacher's role becomes the role of a navigator. This article highlightsthe practice of applying the Heutagogy approach to social study learning.This article recommends the use of the Heutagogy approach to supportstudent autonomy in learning with the aim of increasing the cognitiveinvolvement of students with content and assignments tailored to theindependence, interests, talents and abilities of the students.From the results showed that the Heutagogy approach provides newchallenges, especially for teachers and students in the teaching and learningprocess of social study learning. The Heutagogy approach is recommended tobe used as a starting from elementary to tertiary level with some notes to beconsidered.Keywords: Heutagogy approach, Industrial Revolution 4.0, Social Study